Trends of the Dementia Burden in South Asia: An Analysis of 2021 Global Burden of Disease Study - Shubham Chauhan (21334742) (2025)
Objectives This study aims to analyze the trends in the burden of Alzheimer's Disease and Other Dementias (ADoD) in South Asia from 1990 to 2021, focusing on incidence, prevalence, mortality, and Disability‐Adjusted Life Years (DALYs). The objective is to identify key risk factors, such as metabolic and behavioral health risks, and assess regional variations in the burden of ADoD across five South Asian countries India, Pakistan, Bangladesh, Nepal, and Bhutan. Methods Data from the Global Burden of Disease (GBD) 2021 report were analyzed using descriptive statistics and join point regression analysis. The analysis evaluated trends in ADoD incidence, prevalence, mortality, and DALYs across five South Asian countries, focusing on health risk factors, including high body mass index, behavioral and metabolic risks. Results A slight decrease in incidence rates from 80.57 to 79 per 100,000 was observed, alongside a significant increase in mortality rates from 14.11 to 17.2 per 100,000. While prevalence rates experienced a minor decline, Disability‐Adjusted Life Years (DALYs) rose from 272.02 to 308.27 per 100,000, reflecting an increasing burden of the disease. Notably, Nepal significantly reduced its incidence rates, while Pakistan saw an increase in mortality rates. In South Asia, the highest‐ranking risk factor is metabolic risks, followed by high fasting plasma glucose (FPG). Conclusions The growing burden of ADoD in South Asia necessitates targeted public health strategies addressing key risk factors, with metabolic health risks being a primary contributor. Public health interventions should focus on the most affected populations, particularly the elderly and females, to mitigate the increasing impact of dementia across the region. Other Information Published in: AGING MEDICINE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/agm2.70002